PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI SUB SEKTOR KOSMETIK DAN BARANG KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Azizah, Titin Nur; Nugroho, Mulyanto (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the effect of company size, leverage, and liquidity on company financial performance, with profitability as an intervening variable. The focus of this study is six cosmetic and household goods sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research method used is a quantitative approach with Partial Least Squares (PLS) analysis techniques. The data analyzed include company financial reports, including company size (total assets and total sales), leverage (DER and DAR), liquidity (CuR, QR, and CaR), profitability (ROA, ROE, and NPM), and financial performance (ROI and GPM). The results of the study indicate that leverage has a significant positive effect on financial performance and profitability, while liquidity only has a significant effect on profitability. Interestingly, company size has a significant negative effect on profitability and financial performance. Profitability functions as a significant mediating variable between leverage and liquidity on financial performance. With an R-square of 91.2%, this model shows a strong ability to explain the variability of financial performance. This study provides practical and theoretical contributions to companies and investors in financial management